The Matter of Morality: Examining Moral-Ethics as a Tenet of Transformative Learning - Perdeta L. Bush (Adult Education Research Conference, 2015)
Experience, a common denominator for all adults, is one of the core elements in teaching transformative learning and making meaning (Cranton, 2006). Key in building the educational foundation of transformation, “the way in which individuals make meaning of their experience facilitates growth and learning (Merriam & Brockett, 2007, p. 141). Transformative learning, as an educational theory, calls for the adult learner to re-examine long held beliefs that are built upon personal experiences. Assessing those individual experiences while considering the shared experiences of others may result in a converted frame of reference.